EVALUACIÓN DEL ESPACIO VITAL DE CUYES CRIADOS EN POZAS - Cáceres O., Fernando (2004)
The effect of vital area on productive and reproductive performance was evaluated in 2,325 guinea pigs at IVITA El Mantaro Research Station (300 growing male and female guinea pigs, 750 fattening male and female guinea pigs and 200 female and 25 first mating male guinea pigs). The study was divided in seven assays. Five different vital areas and five different number of animals per well were evaluated in each assay. A total of 25 wells were used for each assay. Different variables (body weight gain, alfalfa intake, feeding convertion index, number of scars due to fights, litter size, mortality and profit/cost index) associated to each productive phase were analyzed. Larger vital areas in assays that involved growing and fattening males resulted in greater body weight gain, lower alfalfa intake, lower feeding convertion index and lower number of scars due to fights. All of these variables showed significant lineal response patterns (p = 0.0001 to 0.02 for growing males and p = 0.0001 to 0.0007 in fattening males). The same pattern was shown for growing females except for body weight gain. For fattening females, weight gain and profit/cost index were adjusted to cuadratic regresion reaching a biological and an economic optimum at 0.19 and 0.18 m2 /guinea pig. The following vital areas were recommended: 0.16 m2 /guinea pig for growing males, 0.14 m2 /guinea pig for growing females, 0.24 m2 /guinea pig for fattening males, 0.18 m2 /guinea pig for fattening females, and 0.28 m2 /guinea pig for breeding animals.